Unexpectedly minor nitrous oxide emissions from fluvial networks draining permafrost catchments of the East Qinghai-Tibet Plateau - Zhang, Liwei; Zhang, Sibo; Xia, Xinghui; Battin, Tom J.; Liu, Shaoda; Wang, Qingrui; Liu, Ran; Yang, Zhifeng; Ni, Jinren; Stanley, Emily H. (Nature Communications, 2022)
Streams and rivers emit substantial amounts of nitrous oxide (N2O) and are therefore an essential component of global nitrogen (N) cycle. Permafrost soils store a large reservoir of dormant N that, upon thawing, can enter fluvial networks and partly degrade to N2O, yet the role of waterborne release of N2O in permafrost regions is unclear. Here we report N2O concentrations and fluxes during different seasons between 2016 and 2018 in four watersheds on the East Qinghai-Tibet Plateau. Thawing permafrost soils are known to emit N2O at a high rate, but permafrost rivers draining the East Qinghai-Tibet Plateau behave as unexpectedly minor sources of atmospheric N2O. Such low N2O fluxes are associated with low riverine dissolved inorganic N (DIN) after terrestrial plant uptake, unfavorable conditions for N2O generation via denitrification, and low N2O yield due to a small ratio of nitrite reductase: nitrous oxide reductase in these rivers. We estimate fluvial N2O emissions of 0.432 − 0.463 Gg N2O-N yr−1 from permafrost landscapes on the entire Qinghai-Tibet Plateau, which is marginal (~0.15%) given their areal contribution to global streams and rivers (0.7%). However, we suggest that these permafrost-affected rivers can shift from minor sources to strong emitters in the warmer future, likely giving rise to the permafrost non-carbon feedback that intensifies warming.